2002
DOI: 10.1007/s101200200036
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sex and racial/ethnic group on the pattern of gastric cancer localization

Abstract: Proximal gastric cancer localization was more frequent among non-Hispanic white men, while non-Hispanic white women had a localization pattern similar to those of other racial/ethnic groups. Proximal gastric cancer represents a distinct subtype of gastric cancer that may have different biology, risk factors, and clinical behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
33
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 16 publications
5
33
0
Order By: Relevance
“…Multiple studies have examined ethnicityrelated differences in survival after gastrectomy, showing prognoses to be superior for Asian and Hispanic patients over their Caucasian and African-American counterparts (17)(18)(19)(20)(21)(22)(23). This trend has been attributed to differences in patterns of disease presentation (i.e., proximal versus distal tumor location), and cultural differences in life style and social habits (17)(18)(19)(20)(21)(22). Interestingly, 2 studies found that patterns of tumor localization among Asians were more similar to the patterns among African Americans than among Caucasians (20)(21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have examined ethnicityrelated differences in survival after gastrectomy, showing prognoses to be superior for Asian and Hispanic patients over their Caucasian and African-American counterparts (17)(18)(19)(20)(21)(22)(23). This trend has been attributed to differences in patterns of disease presentation (i.e., proximal versus distal tumor location), and cultural differences in life style and social habits (17)(18)(19)(20)(21)(22). Interestingly, 2 studies found that patterns of tumor localization among Asians were more similar to the patterns among African Americans than among Caucasians (20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…This trend has been attributed to differences in patterns of disease presentation (i.e., proximal versus distal tumor location), and cultural differences in life style and social habits (17)(18)(19)(20)(21)(22). Interestingly, 2 studies found that patterns of tumor localization among Asians were more similar to the patterns among African Americans than among Caucasians (20)(21). Recognizing the importance of tumor location, that is, proximal tumors tend to follow a more aggressive course, we controlled for location near GE junction in our multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Because our current study is representative nationally, these findings also may be attributed to the typically advanced nature of proximal tumors at presentation or to the possibility that these cancers constitute a different disease. 6,24,25 Yao et al 7 assessed the characteristics and outcome of 301 Hispanic patients with gastric adenocarcinoma among 1897 such patients who were seen at the University of Texas M. D. Anderson Cancer Center. In that study, Hispanics were more likely to be younger, to have distal tumors, and to develop peritoneal metastasis than other ethnicities.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7] Over the past 5 years, 2 population-based analyses, 1 conducted in British Columbia, Canada, and the other in southern California, revealed that self-identified Asian race/ethnicity, including patients of Asian descent, had distinct tumor-related features and a more favorable outcome in compared with individuals from other ethnic backgrounds with the disease. 3,5 Furthermore, a recent retrospective study from the University of Texas M. D. Anderson Cancer Center demonstrated that Hispanic patients with gastric adenocarcinoma displayed unique clinicopathologic features.…”
mentioning
confidence: 99%
“…Tumors located in the proximal third of the stomach are more common in Western countries and patients typically present with more advanced stage disease often due to lack of government supported screening programs (3)(4)(5)(6)(7)(8). The incidence of proximal gastric cancer is on the rise in the United States, most likely related to the obesity epidemic in the United States and prevalence of gastroesophageal reflux disease (9,10).…”
Section: Introductionmentioning
confidence: 99%